2022
DOI: 10.3390/systems10050185
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Research on Three-Player Evolutionary Game in Waste Product Recycling Supply Chain System

Abstract: Recycling channel construction plays an important role in the development of closed-loop supply chains. In particular, the emergence of online recycling channels has made up for the shortcomings of traditional recycling channels with poor information and limited markets. This paper constructs an evolutionary game model to investigate the cooperation between manufacturers and e-commerce platforms with government intervention or not. The result shows that whether an enterprise actively participates in the cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Establishing a closed-loop supply chain model composed of manufacturers, retailers, and network service platforms, Xiang and Xu [18] found that wholesale and sales prices are higher when manufacturers cooperate with network service platforms. Xie et al [19] built an evolutionary game model for a closed-loop supply chain to investigate the cooperations between manufacturers and e-commerce platform, and they found the incentives to join the cooperations depend on the cost of building the recycling system, which can be affected by the government interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing a closed-loop supply chain model composed of manufacturers, retailers, and network service platforms, Xiang and Xu [18] found that wholesale and sales prices are higher when manufacturers cooperate with network service platforms. Xie et al [19] built an evolutionary game model for a closed-loop supply chain to investigate the cooperations between manufacturers and e-commerce platform, and they found the incentives to join the cooperations depend on the cost of building the recycling system, which can be affected by the government interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the abovementioned studies focused on cooperation between manufacturers and different supply chain members but ignored online platforms. Although Xiang and Xu [18] and Xie [19] examined cooperation between manufacturers and platforms, the mode of cooperation they considered is relatively simple, meaning that they did not fully consider the effect of different sales cooperation modes between manufacturers and e-commerce platforms from a perspective of closed-loop supply chains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this paper still has some limitations, and these limitations also provide an opportunity for future research. For example, supply chain members are often partially rational in reality [66,67], thus the impact of fairness concerns on the green supply chain can be studied from the perspective that all supply chain members will be partially rational in the future. In addition, the data used in the numerical simulation come from the existing literature.…”
Section: Conclusion Managerial Implications and Limitationsmentioning
confidence: 99%
“…Therefore, it is necessary to build a recycling channel to save resources to ensure the sustainable development of human society. The recycling channel is particularly important in the dynamic supply chain of the national economy [3]. If there are dual channels in complex supply chain systems, the supply of goods not only ensures the continuous supply of goods from downstream suppliers but also saves the inventory costs of upstream suppliers [4].…”
Section: Introductionmentioning
confidence: 99%